AVOID Game: Developing Educational Media to Prevent Child Kidnapping: English - Mariana Wahyu Listyati; Pramudyani, Avanti Vera Risti; Dwi Hastuti; Ega Asnatasia Maharani (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
The increasing number of child abduction cases has raised concerns among parents regarding children’s safety, particularly within school environments. Early childhood is especially vulnerable to abduction due to limited knowledge and understanding of how to recognize and respond to dangerous situations. This study aims to develop and examine the effectiveness of the AVOID Game as a technology-based educational medium for preventing child abduction in early childhood. The study employed Research and Development (R&D) with a simplified Borg and Gall model consisting of six stages. The participants included school principals, teachers, parents, and early childhood students. Data were collected through interviews, observations, literature reviews, and questionnaires, and analyzed using both qualitative and quantitative techniques. The findings revealed that the AVOID Game was considered feasible as an educational medium based on validation results from material experts (89.2%) and media experts (82.6%). Field trials indicated an improvement in children’s knowledge and understanding of abduction prevention, as reflected in the increase from a pretest score of 74.29 to a posttest score of 84.46. The study concludes that the AVOID Game is effective as an educational medium for preventing child abduction in early childhood while providing an engaging and enjoyable learning experience. The implications highlight the potential of the AVOID Game to be widely implemented as a preventive, technology-based learning strategy.